Moral principles and medical practice: the role of patient autonomy in the extensive use of radiological services. Issue 6 (29th May 2008) - Hofmann, B; Lysdahl, K B
Abstract : There has been a significant increase in the use of radiological services in the past 30 years. There are many reasons for this, but one has received little attention: the increased role of patient autonomy in healthcare. Patients demand x rays, CT scans, MRI, and positron emission tomography scans. The key question in this article is how a moral principle, such as respect for patient autonomy, can influence the extension of radiological services. A literature review reveals how patient autonomy is acknowledged in radiology, and how it is used both to explain and to justify the increase in radiological examinations. Furthermore, it also shows how the premises favouring patients' exercise of their autonomy are not always present, which makes patient autonomy subject to adverse side effects and even abuse. Patient autonomy can be used to reduce the professionals' responsibility for radiological examinations (by avoiding complaints and lawsuits), to increase the popularity of the profession (by giving the people what they want), to increase the income of the professionals or their institutions, and to promote professional activity. Patient autonomy intended to reduce paternalism, to legitimise otherwise morally unjustifiable actions (such as exposure to radiation), and to protect patients, can easily be used as a moral means for opposite ends. These adverse effects are not peculiar to radiology. However, they emerge particularly clearly in explanations and justifications of the substantial increase in radiological services, as well as in debates on overuse of radiological services.